Vietnam Social Accounting Matrix (SAM), 2007 - University of Copenhagen; The World Bank; Central Institute for Economic Management; International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The Vietnam Social Accounting Matrix (SAM) for the year 2007 is based on the newly estimated supply-use tables, national accounts, state budgets, and balance of payments. The SAM reconciles these data using cross-entropy estimation techniques. The final SAM is a detailed representation of Vietnam's economy. It separates 63 activities and commodities; rural/urban labor by different education levels; and households by rural/urban areas and farm/non-farm expenditure quintiles. Labor and household information is drawn from the 2006 Vietnam Household Living Standards Survey. Finally, the SAM identifies government, investment and foreign accounts.